EXPERIENCES AND LESSONS FROM AN INTERNATIONAL PRACTICUM PROGRAM IN UNDERGRADUATE FIELD INSTRUCTION - Kim, Young Ran (Philippine Journal of Social Development, 2011)
This paper outlines the process of organizing social work practicum placements in the Philippines for students from Mokpo National University (MNU), South Korea, in cooperation with the College of Social Work and Community Development, University of the Philippines, Diliman. It presents insights drawn from students’   reports, faculty documents, and the coordinator’s notes. Through two practicums held in 2008 and 2009, participants learned not only social work methods and skills but also cultural awareness and strategies for overcoming their own inadequacies. Overall, the objectives of the program were achieved despite cultural and language limitations. The paper concludes with a discussion of learning gains, limitations and suggestions for future related programs.